2023
DOI: 10.1177/15248380221146800
|View full text |Cite
|
Sign up to set email alerts
|

Factors Correlated With Sexual Assault Victimization Among College Students in the United States: A Meta-Analysis

Abstract: Sexual assault (SA) continues to be a serious problem on college campuses in the United States. This meta-analysis sought to identify correlates for SA victimization on college campuses, as well as examine if there were any differences in correlates for men and women. Database searches utilizing Boolean search terms were used to identify studies to be included in the meta-analysis. Studies were included if they provided quantitative data on correlates for SA victimization among college students. A total of 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Specifically, reviews show that a quarter to more than three-quarter of survivors report experiencing PTSD-related symptoms. Reviews including primary studies with control groups of non-survivors or survivors of other types of trauma report medium to large effect size differences in PTSD symptoms between groups (Van Berlo and Ensink, 2000 ; Classen et al, 2005 ; Wilness et al, 2007 ; Cook et al, 2011 ; Peterson et al, 2011 ; Steine et al, 2012 ; Trevillion et al, 2012 ; Wadsworth and Records, 2013 ; Ba and Bhopal, 2017 ; Chmielowska and Fuhr, 2017 ; Dworkin et al, 2017 , 2023 ; Sparrow et al, 2017 ; Bows, 2018 ; Dworkin, 2018 ; Dame et al, 2020 ; Kahsay et al, 2020 ; Alessi et al, 2021 ; Forkus et al, 2021 ; Gallegos et al, 2021 ; Klein and Martin, 2021 ; Mazza et al, 2021 ; Zarchev et al, 2021 ; Klein et al, 2022 ; Lim et al, 2022 ; Spencer et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, reviews show that a quarter to more than three-quarter of survivors report experiencing PTSD-related symptoms. Reviews including primary studies with control groups of non-survivors or survivors of other types of trauma report medium to large effect size differences in PTSD symptoms between groups (Van Berlo and Ensink, 2000 ; Classen et al, 2005 ; Wilness et al, 2007 ; Cook et al, 2011 ; Peterson et al, 2011 ; Steine et al, 2012 ; Trevillion et al, 2012 ; Wadsworth and Records, 2013 ; Ba and Bhopal, 2017 ; Chmielowska and Fuhr, 2017 ; Dworkin et al, 2017 , 2023 ; Sparrow et al, 2017 ; Bows, 2018 ; Dworkin, 2018 ; Dame et al, 2020 ; Kahsay et al, 2020 ; Alessi et al, 2021 ; Forkus et al, 2021 ; Gallegos et al, 2021 ; Klein and Martin, 2021 ; Mazza et al, 2021 ; Zarchev et al, 2021 ; Klein et al, 2022 ; Lim et al, 2022 ; Spencer et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…More than one in 20 survivors to three-quarter of survivors report anxiety or anxiety-related behavioral changes, such as taking precautions to prevent experiencing another victimization, following the assault. Effect sizes comparing survivors to controls on anxiety symptoms range from small to large (Campbell et al, 2000 ; Ribeiro et al, 2009 ; Chen et al, 2010 ; Peterson et al, 2011 ; Wadsworth and Records, 2013 ; Larijani and Guggisberg, 2015 ; Ba and Bhopal, 2017 ; Chmielowska and Fuhr, 2017 ; Bows, 2018 ; Dworkin, 2018 ; Pulverman et al, 2019 ; Stewart et al, 2019 ; Dame et al, 2020 ; Kahsay et al, 2020 ; Pebole et al, 2021 ; Nicholas et al, 2022 ; Rani et al, 2022 ; Spencer et al, 2023 ). However, in some cases depression and anxiety are combined into one measure resulting in a combined effect size for both.…”
Section: Resultsmentioning
confidence: 99%
“…We can hypothesize on the possible mechanisms leading to this effect. First, this could be partly explained by the fact that SV occurs mainly within couples (Spencer et al, 2023). The fact that SV in two of the included studies occurred solely in the context of IPV provides support to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…An example of these type of factors could be alcohol intake. In fact, individuals with ADHD tend to drink more (Elkins et al, 2018), and in turn, alcohol intake has also been linked to an increase risk of being a sexual victim or perpetrator (Spencer et al, 2023). Of note, this explanation could also be applied to the results on IPV, as it has been shown that alcohol or drugs intake moderates the risk of IPV perpetration or victimization (Wymbs et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Student parties are a place related to all types of GBV, which can be explained by factors related to a campus party culture (e.g. binge drinking, alcohol use, drug use [23] ).…”
Section: Discussionmentioning
confidence: 99%